Toxic Fumes from Shock-Damaged Permissible Explosives - Thomas C. Ruhe; Michael S. Wieland (International Society of Explosives Engineers, 1991)
Marginal detonation of explosives can produce more toxic fumes with higher nitrogen oxides (NOx) than normal detonation. In delay blasting, shock waves from borehole charge explosions can impact those delayed charges still remaining in the delay pattern. This can result in partial desensitization, whereupon the explosive does not misfire, but detonates in a weak unstable fashion releasing a different/unusual spectrum of gaseous reaction products.